1990
DOI: 10.1016/0014-5793(90)81286-w
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐enzyme interactions and their metabolic role

Abstract: There are continuing reports on the existence ofcomplcxes of sequential metabolic enzymes. New techniques for their detection have been described and include afinity electrophorcsis and the use of :mti-idlotypic antIbodIes. Channeling of substrates has been reported for several systems as well as direct substrate transfer through dynamic enzyme associations.Kinetic parameters of metabolic control of organized sjsterns hale been formulated and tested in several systems. These recent results arc expanding our un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…Developments in cell biology have revealed an inhomogeneous cytoplasmic infrastructure at the microscopic level (54,60), in which enzymes are highly organized (19 -22, 43). In particular, it has been demonstrated that glycolytic enzymes can bind together to form a multienzyme complex (8,19,42) associated with F-actin (8,64) or other sites such as microtubules and the cellular membrane (24,36). The metabolic advantages of these multienzyme complexes include metabolic channeling, which refers to the transfer of products from an enzyme directly to an adjacent active site without entering the bulk solution (4,32,45,49).…”
Section: Discussionmentioning
confidence: 99%
“…Developments in cell biology have revealed an inhomogeneous cytoplasmic infrastructure at the microscopic level (54,60), in which enzymes are highly organized (19 -22, 43). In particular, it has been demonstrated that glycolytic enzymes can bind together to form a multienzyme complex (8,19,42) associated with F-actin (8,64) or other sites such as microtubules and the cellular membrane (24,36). The metabolic advantages of these multienzyme complexes include metabolic channeling, which refers to the transfer of products from an enzyme directly to an adjacent active site without entering the bulk solution (4,32,45,49).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it has become evident that there is a high degree of organization where different lipid and protein structures associate among themselves and with other molecules. The high molecule concentration found in the cytoplasm promotes macromolecule associations such as protein-protein, protein-membrane, protein-nucleic acid, protein-polysaccharide and thus is a control factor for all biological processes (Srere & Ovadi, 1990). Indeed, the classical studies by Green (Green et al, 1965), Clegg (Clegg, 1964) 102 and Fulton (Fulton, 1982) have suggested that enzymes are not dispersed in the cytoplasm.…”
Section: Metabolons: Enzyme Complexes That Channel Substratesmentioning
confidence: 99%
“…Channeling requires stable interactions of the multienzymatic metabolons (Al-Habori, 2000;Cascante et al, 1994;Ovadi & Srere, 1996;Ovadi & Saks, 2004;Srere & Ovadi, 1990;Srere, 1987). The metabolon stability is facilitated by the compartmentalization of the cell in different organelles and structures (Jorgensen et al, 2005).…”
Section: Metabolons: Enzyme Complexes That Channel Substratesmentioning
confidence: 99%
“…The first reason is that the system is in quasi-equilibrium, that is (14) where K,, K:, K,, Ki are real dissociation constants. This situation is trivial and need not be discussed.…”
Section: The Modelmentioning
confidence: 99%